IMPLEMENTASI SISTEM PEMBUKTIAN TERBALIK DALAM TINDAK PIDANA PENCUCIANUANG DI INDONESIA - Chotibul Umam; Tofik Yanuar Chandra; Mohamad Ismed (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The issue examined in this thesis concerns the analysis of the implementation and challenges in applying the reverse burden of proof system in money laundering crimes in Indonesia, using the Law Enforcement Theory and the Proof Theory. The reverse burden of proof system is a special mechanism in criminal procedural law that obliges the defendant to prove that the assets alleged are not derived from criminal acts, as regulated in Articles 77 and 78 of Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes. The method used in this research is normative legal research conducted as an effort to obtain the necessary data related to the problem. The data used consists of secondary data and tertiary legal materials. In addition, primary data is also used to support the secondary legal materials. Data analysis is carried out using qualitative juridical analysis methods. The research results show that the implementation of the reverse burden of proof system has a clear legal basis and is limited and balanced, where the Public Prosecutor remains obligated to prove the elements of the crime of money laundering, while the defendant is burdened with the obligation to explain the origin of their wealth. There are several rulings where judges have given defendants the opportunity to prove ownership of the wealth, but based on the evidence submitted at trial, the panel of judges concluded that the defendants could not prove that the wealth was obtained through lawful acts or did not originate from a crime or offense. This construction does not eliminate the presumption of innocence but serves as a special instrument to strengthen evidence in complex cases. However, its implementation still faces various challenges, including potential conflicts with human rights protection principles, the absence of uniform technical guidelines, disparities in judicial interpretation, and limited capacity of officials in financial investigations. Therefore, strengthening technical regulations and enhancing law enforcement capacity are necessary to ensure this system operates optimally and aligns with the principles of the rule of law.